Effects of nano TiO2 on properties of rice husk ash mortars - Noorvand, Hassan (2013)
Abstract: The effect of nano TiO2 on untreated rice husk ash (RHA) mortars was investigated. The enhancement effect of treated RHA as a cement replacement on properties of cement composites has been extensively studied whereas the use of field burnt and untreated RHA has shown undesirable effect on the characteristics of cement-based materials due to the weak pozzolanic nature of untreated RHA. In this study, field burnt black rice husk ash denoted as BRHA was used as cement replacement in fractions of 10%, 20% and 30% of the mortar volume. To compensate the adverse effect of BRHA, 0.5%, 1% and 1.5% nano TiO2 were added into BRHA cement mortars. The mechanical properties were studied using the compression test and the results compared to a non-destructive method using ultrasonic pulse velocity at the age of 7, 28 and 90 days of curing. Water absorption and SEM tests were performed to study microstructural changes of hardened cement mortars at 7, 28 and 90 days. XRD, TGA and DSC tests were carried out to investigate the chemical composition of BRHA mortars with and without nano TiO2. The results indicated that incorporating nano TiO2 in blended cement with BRHA improved the mechanical properties and microstructure of BRHA mortars. Among the three different fractions of nano TiO2, addition of 1.5% nano TiO2 produced the highest value of compressive strength at all ages in comparison with 0.5% and 1% of nano TiO2-BRHA mixtures. For example, compressive strength of 10% BRHA mix with 1.5% nano TiO2 was 13% higher than that of control sample at 28 days. This was attributed to better particle packing of BRHA mortars with the presence of 1.5% nano TiO2. SEM images indeed showed improvement in the interfacial transition zone (ITZ) and density microstructure of BRHA mortars containing 1.5% nano TiO2. Moreover, a higher rate of pozzolanic activity of BRHA mortars was observed when 1.5% nano TiO2 was added. XRD results showed higher degree of CH consumption for BRHA mortars containing 1.5% nano TiO2 in comparison with BRHA mortars at 28 days. TGA results further confirmed the better pozzolanic behaviour for 1.5% nano TiO2-BRHA mixes compared to BRHA mixes with and without 0.5% and 1% nano TiO2. The results from DSC indicated that the well-crystalline structure of CH compound of BRHA mixes was transformed to the ill-crystalline phase when nano 1.5% TiO2 was added, which accounts for the superior pozzolanic activity of BRHA mortars with presence of 1.5% nano TiO2.